Pengaruh Harga Terhadap Kepuasan Pelanggan Nasi Jamblang di Kota Cirebon Provinsi Jawa Barat - Ramadhani, Tantya Shifa; Sabila, Difa Madani; Wachdijono, Wachdijono (Agropross : National Conference Proceedings of Agriculture, 2023)
Customer satisfaction is the attitude of the customer after buying/consuming a product. Therefore every entrepreneur strives to be able to build, achieve and maintain customer satisfaction, so that his business is sustainable. This study aims to examine the effect of cost on customer satisfaction of jamblang rice in Cirebon City, West Java Province with dominant indicators reflecting these two variables. This research was conducted from April to May 2023 using a descriptive quantitative research design and survey method. The research population is an infinite number of jamblang rice customers in Cirebon City, therefore the technique for determining the number of samples is based on a predetermined loading factor which is equal to 0.6 so that the total sample is 100 respondents. Data analysis uses the Structural Equation Model instrument. The results of the study concluded that price has a real and positive influence on customer satisfaction (0.77) and the indicator that is most involved in price is "recommending prices to others" while for customer satisfaction is "fulfilled expectations". The results of this study are useful for the development of knowledge on customer behavior and can be a recommendation for jamblang rice business people in Cirebon City in order to achieve and or maintain customer satisfaction.